Dependência de internet na aceitação e uso de um ambiente virtual de aprendizagem - Terra, Jefferson Azevedo (2015)
This research analyzes the growth in the use of technological tools such as the Internet in everyday life of people and the consequent modifications generated by the intensive use of this tool. Using internet generates benefits for the education area by providing communication facilities and the creation of virtual learning environments. However, the constant use of the Internet can also cause dependency and result in damage to the academic environment, professional and even in interpersonal relationships of the users. The objective of this study was to examine whether there is a significant difference between dependent users and internet not dependent to the determinants of UTAUT theory for the intended use of a virtual learning environment. One Survey research to identify the dependency level of each student and also the existence of differences was conducted between gender, age, chosen course and situation on the labor market. Thus, students were classified into two groups according to the level of Internet addiction. The first was formed by the dependent students and the second was built by students who did not have internet addiction. The Student t test and chi square test were used to compare the groups and the results confirmed that there was significant difference when evaluated the four determinants of acceptance and use of UTAUT technology theory. The results allow us to identify not dependent students have lower average for facilitating conditions, in addition, this group of students dedicated more effort to learn how to use Moodle. The result of this process is that this group values the technological tool and believes that it will help them get better academic performance. Finally, the dependent students have lower averages for social influence and do not identify so strongly that people they consider important think they should use the Moodle virtual learning environment.